The Book of Delight, and other papers - Abrahams, Israel, 1858-1925 (Salt Lake City, UT : Project Gutenberg, 2006)
"The Book of Delight and Other Papers" by Israel Abrahams is a collection of essays and addresses written in the early 20th century. This work offers insights into Jewish folklore, literature, and culture, exploring themes relevant to Hebrew and Jewish thought while weaving together various narratives and proverbs that reflect the complexities of Jewish identity and experience. The opening of the collection introduces "The Book of Delight," which portrays a poetical romance attributed to Joseph Zabara, an influential figure from around the year 1200. Abrahams discusses Zabara$1 (Bs unique literary style that merges folk tales with imaginative poetry, emphasizing his contributions to Hebrew literary tradition. The text begins a fascinating journey where the character Joseph meets Enan, a giant figure who initially presents himself as a friend but is revealed to have a more complex nature blending wit and wisdom with darker undertones. The narrative is enriched with fables that explore the human condition and relationships, particularly contrasting themes surrounding women and romance, drawing from both ancient wisdom and personal anecdotes. This opening sets the stage for a deeper exploration of human interactions, morality, and the power of storytelling. (This is an automatically generated summary.)s
"The Book of Delight" -- A visit to Hebron -- The solace of books -- Medieval wayfaring -- The fox's heart -- "Marriages are made in heaven" -- Hebrew love songs -- A handful of curiosities: George Eliot and Solomon Maimon. How Milton pronounced Hebrew. The Cambridge Platonists. The Anglo-Jewish Yiddish Literary Society. The mystics and saints of India. Lost Purim joys. Jews and letters. The shape of Matzoth.
Release date is 2006-02-01
Produced by Tom Allen, Charles Franks and the Online Distributed Proofreading Team
Keywords: Ibn Zabara, Joseph ben Meir, 1140?- Sefer sha'ashu'im; Jews -- Intellectual life; Love poetry, Hebrew -- History and criticism